Novo-desenvolvimentismo, governo Lula e o programa de aceleração do crescimento: uma análise critica - Costa Júnior, Francisco José Aguiar (2012)
The Economic development is a theme in the economic literature since the Classical School. After the World War II, in the beginning of the Fordist accumulation regime, raised an extensive literature about the underdevelopment in peripheral countries. These authors had emphasized the importance of the industrialization and infrastructure investments for overcome underdevelopment. In Brazil, during the same period, Celso Furtado had diagnosed roots of underdevelopment using the historical and structural method and emphasizing the role of the state for the construction of a national development policy to overcome underdevelopment. Furtado was the main influencer of the developmentalist national ideology that dominated both the economic literature as development policies (during the period of import substitution process) adopted in Brazil until the early 1980s. With the crisis of the Fordist regime and the beginning of the accumulation of financial dominance, the literature about the economic development was relegated to the neoliberal policies that started to dominate the agenda of the government. In Brazil, the consequence of this new regime of accumulation was the foreign debt crisis in the 80s. With the economic reforms that occurred in the '90s, culminating with the creation of the Real Plan, the country entered in the peripheral liberal model, no longer being treated as a 'underdeveloped country' and passing to be considered as an 'emerging market' country. The Real Plan was efficient to control inflation, but had a very high social cost. In 2003, Lula became the president of Brazil adopting the same neoliberal policies of the Cardoso government, frustrating the expectations of their voters. In 2007, President Lula was reelected and, early in his second mandate launched the Growth Acceleration Program (PAC), claiming to be a development program and promising to invest in infrastructure to generate economic growth with social equity. A group of Brazilian economists called new- developmentalists identified the PAC as a rupture with neoliberal policies in Brazil and a return of the state in the economy playing an essential role on promoting development. In fact, it was found that Lula’s second government was better in terms of socioeconomic indicators than the first. This dissertation did a critical analysis of the PAC, of the Lula government and the of new developmentalism. It identified, also, a theoretical decline of the new- developmentalists compared with the theories that prevailed in the period of national developmentalism. It verified that the reasons of the second Lula government have been better than the first was less because of to the PAC, and more for external issues, mainly the effect China. It also identified that the PAC, which was proposed to be a development program, has institutional arrangements with liberal tendencies, besides emphasizing investments in infrastructure only in the commodities sector, corroborating the reprimarization of the exportation and expanding the structural external vulnerability of the Country . Finally, we found that, despite investments in infrastructure be essential for the development of the country, the balance of four years of the PAC results showed results much weaker than expected, having, including, inflated datas by the government.